The specificity of research methods in Environmental Protection - Orzeszek, Piotr; Jerzak, Maja (Studia Ecologiae et Bioethicae, 2011)
The article pertains to the methodological status of the Environmental Protection and the specificity of the research methods in this science. The Environmental Protection has recently become a recognized scientific discipline in Poland. As opposed to other European countries, it has been qualified as belonging to three fields of science. The current moment is the time of its formation and development as a scientific discipline. Separating it from other scientific disciplines evokes questions regarding its methodological connections with its mother disciplines. The research methods used in the Environmental Protection are similar to the methods applied in the discipline of chemistry, natural sciences, and agriculture. The aforementioned methods possess also other specific features, take the example of the fact that they are regulated by the law, and benefit from the technologically advanced examination apparatus. The article describes the selected methods in the Environmental Protection and poses the question regarding the methodology applied in this science.